Morning blood pressure surge increases in patients with hypertensive primary hyperparathyroidism and is independently associated with serum calcium level. (2nd January 2020) - Demirtas, Derya; Sumbul, Hilmi Erdem; Demirtas, Abdullah Orhan; Icen, Yahya Kemal; Gulumsek, Erdinc; Koca, Hasan; Urgun, Örsan Deniz; Koc, Mevlut
ABSTRACT: Introduction : There is not enough data on the effects of primary hyperparathyroidism (pHPT) on morning blood pressure surge (MBPS) in the literature. We aimed to determine whether there was any change in MBPS value in patients with hypertensive pHPT and to determine the parameters related to MBPS. Method : 80 patients with newly diagnosed pHPT with hypertension (HT) and 80 controls with newly diagnosed hypertension were included. Routine laboratory examinations and ambulatory blood pressure monitoring (ABPM) were performed in all patients. Results : In patients with pHPT, blood urea nitrogen (BUN), triglyceride, hs-CRP, uric acid, serum calcium (Ca), parathormone (PTH), daytime SBP and MBPS levels are higher than others (p < 0.05). Body mass index (BMI) and Ca level were independently associated with MBPS. In patients with MBPS ≥ 25 mmHg, BMI, BUN, creatinine, uric acid, Ca and PTH levels were found to be higher than others. BMI values and Ca levels determine the patients with MBPS ≥ 25 mmHg (p < 0.05) independently. According to this analysis, increase in BMI (for each 1 unit) and Ca level (for each 0.1 mg/dL) was found to increase the probability of MBPS ≥ 25 mmHg by 17.8% and 7.7%, respectively. When the cut-off value for Ca was taken as 10 mg/dL, the patients with MBPS ≥ 25 mmHg were determined with 73.5% sensitivity and 73.1% specificity. Conclusion : MBPS significantly increases in patients with newly diagnosed hypertensive pHPT. This increase in MBPS is closely associated with increased Ca levels. In patients with pHPT, lowering the Ca level below 10 mg/dL may have clinical implications.